Total synthesis of thioamycolamide A via a biomimetic route. Issue 41 (8th October 2020) - Pan, Chengqian; Kuranaga, Takefumi; Kakeya, Hideaki
Abstract : A concise total synthesis of thioamycolamide A was accomplished as a key step of thio-Michael addition via a biomimetic route. Abstract : Thioamycolamide A is a biosynthetically unique cytotoxic cyclic microbial lipopeptide that bears a d -configured thiazoline, a thioether bridge, a fatty acid side chain, and a reduced C-terminus. Based on the biosynthetic insights, a concise total synthesis of thioamycolamide A was accomplished.